2017
DOI: 10.1097/lbr.0000000000000362
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Learning Perspectives of Pulmonary Fellows and Practitioners

Abstract: Pulmonary fellows and practitioners we surveyed preferred a traditional course structure with cadaver/animal models and high-fidelity simulation training as compared with a flipped classroom model and low-fidelity simulators, but whether this holds true for the wider population is unknown. Larger studies are needed to validate learning perception with outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…A recent survey showed that fellows and practitioners preferred a traditional course structure with a high-fidelity training course to a flipped classroom model and low-fidelity simulators. [13] The 30-minute lecture followed by a hands-on session might contribute to a better understanding of the procedure. In the hands-on session with a biosimulator, subjects can review their skills immediately.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey showed that fellows and practitioners preferred a traditional course structure with a high-fidelity training course to a flipped classroom model and low-fidelity simulators. [13] The 30-minute lecture followed by a hands-on session might contribute to a better understanding of the procedure. In the hands-on session with a biosimulator, subjects can review their skills immediately.…”
Section: Discussionmentioning
confidence: 99%